(untitled) (Plant Tissue Culture and Biotechnology, 2026)
Genetic diversity analysis of seven BARI masur (BM) lentil varieties from Bangladesh was performed using polymerase chain reaction (PCR) with the random amplification of polymorphic DNA (RAPD) technique. Seventy-six unique bands were obtained using 16 of the 20 randomly selected decamer oligonucleotide primers, with an average of 4.75 bands per primer. Ten primers were found to be 100% polymorphic based on the observed banding patterns. Significant genetic variation is evident, as evidenced by pairwise genetic distances ranging from 0.1563 to 0.6931. Seven lentil varieties have been divided into three main clusters via a dendrogram based on Nei’s genetic distance using the Unweighted Pair Group Method of Arithmetic Means (UPGMA), with a similarity coefficient of 0.5198. Cluster 1 consisted of BM-1, BM-2, BM-3 and BM-5, cluster 2 consisted of BM-4 and BM-7 whereas only BM-6 was found in cluster 3. Cluster 1 was further grouped into three sub-clusters and the varieties BM-1 and BM-2 were placed in the same sub-cluster, whereas the varieties BM-3 and BM-5 were placed in separate sub-clusters. The varieties BM-1 and BM-2 showed relatively less divergence among the varieties of the cluster 1. Conversely, BM-6 variety was presented in a separate cluster that indicates this variety is more divergent than the other varieties. Plant Tissue Cult. & Biotech. 35(2): 371-380, 2025 (December)